2020
DOI: 10.3390/molecules25122811
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Mushrooms and Their Lignocellulolytic Enzyme Production Through the Utilization of Agro-Industrial Waste

Abstract: A large amount of agro-industrial waste is produced worldwide in various agricultural sectors and by different food industries. The disposal and burning of this waste have created major global environmental problems. Agro-industrial waste mainly consists of cellulose, hemicellulose and lignin, all of which are collectively defined as lignocellulosic materials. This waste can serve as a suitable substrate in the solid-state fermentation process involving mushrooms. Mushrooms degrade lignocellulosic substrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 230 publications
(225 reference statements)
0
81
0
1
Order By: Relevance
“…A perusal of data presented in Table 2 showed that paddy straw inoculated with bajra grain spawn proved to be the best as it resulted in the formation of the highest number of sporophores (20.6). This may be due to multilateral enzyme system of M. gigantea, which biodegrades a large range of lignocellulosic wastes (Kumla et al, 2020). The lowest number of sporophores (17.0) were recorded on wheat straw inoculated with maize grain spawn (Table 2).…”
Section: Assessment Of Growth Behaviourmentioning
confidence: 96%
“…A perusal of data presented in Table 2 showed that paddy straw inoculated with bajra grain spawn proved to be the best as it resulted in the formation of the highest number of sporophores (20.6). This may be due to multilateral enzyme system of M. gigantea, which biodegrades a large range of lignocellulosic wastes (Kumla et al, 2020). The lowest number of sporophores (17.0) were recorded on wheat straw inoculated with maize grain spawn (Table 2).…”
Section: Assessment Of Growth Behaviourmentioning
confidence: 96%
“…Mushrooms produce a vast set of extracellular carbohydrate-active enzymes and biological active molecules that degrade very complex compounds such as hemicellulose and lignin. The variety of enzymes is dependent on the habitat and specific substrates, so it differs among mushroom species and home ground [45].…”
Section: African Mushroomsmentioning
confidence: 99%
“…The increase in wastes from agriculture directly relates to the world's population growth and the consequent rising demand for food production. A good alternative to recycle these wastes is through their use in the formulation of substrates for the cultivation of edible mushrooms (KUMLA et al, 2020).…”
Section: Abstract: Oyster Mushroom; Fungal Protein;mentioning
confidence: 99%
“…Accordingly, colonization and production of fruiting bodies in lignocellulosic substrates are directly related to the fungus mycelium vigor (FIGUEIRÊDO; DIAS, 2014). Another reason is the nutritional characteristics of the substrate and the environmental conditions of the cultivation process, as reviewed by KUMLA et al (2020). Indeed, the C/N ratio of the wastes used to formulate the substrates to cultivate Pleurotus spp.…”
Section: Biological Efficiency (Be) and Mushroom Yieldmentioning
confidence: 99%